Effects of biochar and inorganic fertiliser on the growth and yield of beetroot (Beta vulgaris L.) in Kenya - Kwizera, E.; Opiyo, A. M.; Mungai, N. W. (International Journal of Horticultural Science, 2023)
Beetroot (Beta vulgaris L.) is a root vegetable packed with many nutritional benefits such as minerals and vitamins. Despite its importance in Kenya, farmers get about 30-35 t/ha which is significantly lower than the potential yield (68 t/ha). This is mostly attributed to low soil fertility. This study aimed to determine the response of the beetroot growth and yield on biochar and NPK. A 3×4 factorial experiment was carried out at Egerton University farm over two seasons to test the effects of biochar and NPK (17-17-17), under supplemental irrigation. Biochar (0, 5, 10 t/ha) was combined with NPK (0, 200, 300, 400 kg/ha). The combination of Biochar and NPK increased significantly (p ≤ 0.05) beetroot growth and yield in two seasons. Treatment B10N400 showed the tallest plants (79.2 cm) at 90 days in season two, while the control resulted in the shortest (27.6 cm). Treatment B10N200 showed the biggest (213.2 cm2) leaves at 90 days. The treatment B5N300 recorded the highest marketable yield (84 t/ha) in season two and the lowest was B0N0 with 2.6 t/ha. Sole application of NPK rates (200, 300, 400 kg/ha) increased significantly the growth and yield of beetroot compared to the control in both seasons. In season one, N300 (300 kg/ha) had 61.9 t/ha of the total yield, the control had the lowest. In season two, 300 kg/ha had 83 t/ha of total yield. Biochar increased beetroot growth and yield in season 2. Treatment B5 recorded the highest marketable yield of 61.2 t/ha, while the control showed the lowest of 53 t/ha.